2001
DOI: 10.1080/00380768.2001.10408387
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen mineralization of silk waste applied to soil under aerobic conditions

Abstract: Silk waste which is a byproduct of silk reeling consists mainly of silk proteins such as sericin and fibroin. Although silk waste has a high N content (164 g kg-I) and low CjN ratio (2.16), net N mineralization in soil at 30"C under aerobic conditions was very slow (21.4% in 184 d). The N mineralization rate of silk waste applied to soil after hydrolysis with HCI was higher than that of untreated silk waste. The effect of hydrolysis with 0.2 M HCI for 60 min at 9TC on the net N mineralization for 56 d was twic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…It could be suggested that, from this week onward, the multilayer coating tended to release this nutrient more easily. However, it is also possible that these forms of nitrogen are associated with protein degradation in soil [54].…”
Section: Nutrient Release In Soilmentioning
confidence: 99%
See 2 more Smart Citations
“…It could be suggested that, from this week onward, the multilayer coating tended to release this nutrient more easily. However, it is also possible that these forms of nitrogen are associated with protein degradation in soil [54].…”
Section: Nutrient Release In Soilmentioning
confidence: 99%
“…It could be suggested that, from this week onward, the multilayer coating tended to release this nutrient more easily. However, it is also possible that these forms of nitrogen are associated with protein degradation in soil [54]. After studying the cumulative amounts of leached nutrients (Figure 10C,D), it was established that the coating was able to reduce the amount of NPK and inorganic nitrogen leached from week 1.…”
Section: Nutrient Release In Soilmentioning
confidence: 99%
See 1 more Smart Citation
“…Silk waste is a byproduct from silk reeling and is a residual part of the cocoon. Although silk waste has a high N content, its N mineralization in soil is much slower than those of other biomaterials because it has the crystal structure of silk protein, and thus it can be utilized as a slow-release fertilizer (Murase & Yonebayashi, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Nutrient release of polyolefincoated fertilizer depends on the reaction of the coating component to physical factors such as temperature and the process of diffusion (Gandeza et al, 1991). Silk waste is decomposed and mineralized by soil microbes (Murase & Yonebayashi, 2001).…”
Section: Introductionmentioning
confidence: 99%